2019
DOI: 10.3390/polym11030471
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of bFGF on the Fabrication of Microencapsulated Cartilage Cells under Different Shaking Modes

Abstract: Cell encapsulation in hydrogels has been extensively used in cytotherapy, regenerative medicine, 3D cell culture, and tissue engineering. Herein, we fabricated microencapsulated cells through microcapsules loaded with C5.18 chondrocytes alginate/chitosan prepared by a high-voltage electrostatic method. Under optimized conditions, microencapsulated cells presented uniform size distribution, good sphericity, and a smooth surface with different cell densities. The particle size distribution was determined at 150–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…On account of cell-based research and treatment, the demand for cartilage cells is quickly increasing. However, there is still a lack of full understanding of pathophysiology and delays in diagnosis due to the avascular character of cartilage, the neural structure of the tissue, and obstacles connected with providing potential therapies [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…On account of cell-based research and treatment, the demand for cartilage cells is quickly increasing. However, there is still a lack of full understanding of pathophysiology and delays in diagnosis due to the avascular character of cartilage, the neural structure of the tissue, and obstacles connected with providing potential therapies [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of 3D culture techniques has grown dramatically, resulting in the creation of several applications. For example, hydrogels have similar qualities to natural ECMs, such as biocompatibility, biodegradability, and adjustable properties (such as shape, gel state, and mechanical strength) (Hwang et al, 2009;Lei et al, 2011a;Lei et al, 2011b;Smeriglio et al, 2015;Zhou et al, 2019;Wang et al, 2021a;Fournier and Harrison, 2021;Ma et al, 2021;Okita et al, 2021). In recent years, hydrogels have gotten much interest in tissue engineering research, and they are the 3D culture materials we will primarily discuss.…”
Section: D Vs Traditional 2d Cell Culture: Strategy and Advantagementioning
confidence: 99%
“…Frontiers in Bioengineering and Biotechnology frontiersin.org Inanc et al (2006) hDPSCs Li et al (2017) An effective method for the production of hPDLF-PLGA and hDPSCs-PLGA constructs with increased osteogenic and odontogenic differentiation potential technologies constitute a novel paradigm for the organization of a wide range of tissues, including cartilage regeneration (Zhou et al, 2019), artificial vascular construction (Rouwkema and Khademhosseini, 2016), and generation of various organ tissues (Herranz et al, 2013;Luo et al, 2013;Zhang et al, 2014;Salerno-Goncalves et al, 2016) and cancer spheroids (Qian et al, 2008;Ulbrich et al, 2011;Ma et al, 2014). Furthermore, these aggregates are utilized to research the molecular pathways involved in angiogenesis (Rouwkema and Khademhosseini, 2016), osteogenesis (Braveboy-Wagner and Lelkes, 2022;Masini et al, 2022), cancer formation (Ma et al, 2014;Dietrichs et al, 2022), and pharmacological testing (Nishikawa et al, 2005) (Figure 2).…”
Section: Hydrogel-based 3d Cell Model For Tissue Formation Dysfunctio...mentioning
confidence: 99%
“…For example, Costantini D et al ( Costantini et al, 2019 ) studied the effects of microgravity on human bile duct trunk/progenitor cells (HBTSCs) and found that stem gene expression in HBTSCs cultured in SMG microgravity conditions was significantly increased compared with HBTSCs cultured under normal gravity control conditions. Zhou X et al ( Zhou et al, 2019 ) fabricated microencapsulated cells through microcapsules loaded with C5.18 chondrocytes alginate/chitosan prepared by a high-voltage electrostatic method. It could be found from the cell viability (cell proliferation) cell proliferation (AO/EB staining) and cell viability (CCK-8 assay) results that microencapsulated cells had a better cell proliferation under 3D micro-gravity microgravity conditions using bFGF than under 2D conditions (including static and shaking conditions).…”
Section: Introductionmentioning
confidence: 99%